Evaluation of the antifungal, antibacterial, and anti-inflammatory activity of a halophyte plant Arthrocnemum macrostachyum Koch extracts. - Eijaz, Sana; Khan, Muneeba; Mirza, Amber; Parveen, Anjum; Mansuri, Shazia; Muhammad Nadir (International Journal of Endorsing Health Science Research, 2021)
Background: Indiscriminate use of conventional antibiotics has become a major factor responsible for the emergence and dissemination of multidrug-resistant strains of microorganisms. In this regard, we analyzed the plant extracts as an alternative solution for the inhibition of the resistant bugs. Methodology: This study was planned to investigate the antifungal, antibacterial and anti-inflammatory activities of hexane, ethyl acetate, chloroform, and methanol extracts of Arthrocnemum macrostachyum. Soxhlet apparatus was used to prepare different extracts of the whole plant using hexane, ethyl acetate, chloroform, and methanol. The antifungal and antibacterial activity was analyzed with the help of a good diffusion technique using different concentrations of plant extracts. The anti-inflammatory activity was also checked by observing the inhibition of albumin denaturation. Results: Maximum antifungal activity was observed by hexane, methanol, and chloroform extracts, and maximum antibacterial activity showed by the methanol extract. The most sensitive fungi found were Mucor, Aspergillus flavus, Saccharomyces, and Candida. Trichophyton mentagrophytes were found resistant to all the extracts. The most sensitive bacterial isolates found were Salmonella typhi, Proteus mirabilis, Pseudomonas aeruginosa, and Citrobacter freundii. The most resistant organisms were Streptococcus fecalis and Shigella dysenteriae. Methanol and chloroform extracts produced observable anti-inflammatory potential by inhibiting albumin denaturation. Statistical analysis was performed on SPSS version 23.0. Conclusion: The plant extracts showed significant antifungal, antibacterial and anti-inflammatory activity. These findings may support using the Arthrocnemum macrostachyum whole plant as an anti-inflammatory, antibacterial, and traditional antifungal plant. Our results demonstrate that this plant has considerable therapeutic effects on potential infectious agents and can be used to alternative conventional medicines.